2016
DOI: 10.1111/ppa.12565
|View full text |Cite
|
Sign up to set email alerts
|

Diversity of genusLasiodiplodiaassociated with perennial tropical fruit plants in northeastern Brazil

Abstract: Until now, only Lasiodiplodia theobromae has been reported in association with gummosis and dieback of cashew plants and other tropical fruit plants in northeastern Brazil. This study aims to identify and characterize species of Lasiodiplodia associated with gummosis and dieback on tropical fruit plants grown in Cear a, Para ıba, Pernambuco, Piau ı and Rio Grande do Norte States in northeastern Brazil with a description of two new species: Lasiodiplodia caatinguensis sp. nov. and Lasiodiplodia pontae sp. nov. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
54
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 73 publications
(58 citation statements)
references
References 37 publications
3
54
0
1
Order By: Relevance
“…Similarly, L. pseudotheobromae was the more virulent species on A. muricata , but could not be differentiated from the other species on atemoya. This may be attributable to a possible variation in levels of virulence between different isolates of the same species, as has already been observed for Macrophomina (Claudino & Soares, ); alternatively, each host may have responded differently to infection by each species, as was demonstrated by Coutinho et al () and Zlatković et al (). In future studies, these hypotheses could be verified by cross inoculation of the same isolates in these three hosts.…”
Section: Discussionmentioning
confidence: 75%
See 2 more Smart Citations
“…Similarly, L. pseudotheobromae was the more virulent species on A. muricata , but could not be differentiated from the other species on atemoya. This may be attributable to a possible variation in levels of virulence between different isolates of the same species, as has already been observed for Macrophomina (Claudino & Soares, ); alternatively, each host may have responded differently to infection by each species, as was demonstrated by Coutinho et al () and Zlatković et al (). In future studies, these hypotheses could be verified by cross inoculation of the same isolates in these three hosts.…”
Section: Discussionmentioning
confidence: 75%
“…The other known species less frequently isolated were L. brasiliense , L. crassispora , L. hormozganensis , L. subglobosa and L. theobromae , which have already been reported in Brazil as being associated with several hosts (Netto et al , ,; Machado et al , ; Correia et al , ; Poletto et al , ; Rosado et al , ; Coutinho et al , ; Farr & Rossman, ). In the literature, it has been speculated that the wide range of hosts for L. theobromae exceeds 500 worldwide.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…in fruit-producing orchards and under post-harvest conditions in northeastern Brazil showed that Lasiodiplodia theobromae (syn. Botryodiplodia theobromae) is present in all areas studied, being the most frequent species associated with dieback, gummosis, leaf spot, stem-end rot and fruit rot symptoms (Netto et al, 2014;Correia et al, 2016;Coutinho et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, fungal diseases affecting cashew, mango, papaya and grapevine crops have been reported in northeastern Brazil, with prevalence of infections caused by members of the family Botryosphaeriaceae (Netto et al, 2014;Correia et al, 2016;Coutinho et al, 2017). Botryosphaeriaceae species are important pathogens of native and non-native plants worldwide (Slippers & Wingfield, 2007;Phillips et al, 2013).…”
Section: Introductionmentioning
confidence: 99%